Local tubers and beans processing innovation for micro enterprises diversification. (February 2019) - Lutfi, M; Hermanto, M B; Luqman, A; Sulistyaningsih, W I; Prajogo, U
Abstract: Local commodities such as tubers and beans are abundant throughout Indonesia, but its economic value is low and still only a minor source of income for the rural areas community. The purpose of this study was to improve technological access of inferior local tubers and beans processing thus increasing the added value and facilitates the community economic revenues. The first step of this study was conducted to identify the nutrients content of local commodities correspond to the requirements of food bars production. The second stage done to seek the composition of each component i.e. sweet potato flour, cowpea flour, and mung beans flour and also konjac flour addition to reach a good food bars characteristics. The product was then evaluated in terms of product appearance, nutritional value, and acceptance by consumers. The outcome of this study was to utilize local commodities convert to product that can be adopted by the rural community. The result show that the composition of sweet potato flour, cowpea flour, and mung bean flour of 50: 20: 30 with the addition of 25 grams konjac flour was the best composition. Glucomannan of konjac flour affects to the quality of food bars especially to its strength.